Rock Slope Stability Analysis Using Photogrammetric Method At Hume Cement Quarry, Gopeng, Perak - Juhari, Aisyah Shahirah (Universiti Sains Malaysia, 2018)
This project focused on rock slope stability analysis at Hume Cement Quarry by using photogrammetry method and analysis data by Dip 7.0 program in rocscience. Quarry is a common place which is instability of the rock slope happen as the big issues due to the activities on site work such as excavation and blasting where it creating fractures, faults, and joints. In this project, several kinds of analysis are taken to investigate the stability of the rock slope whether it might be fail or not. There are two methods used which is empirical analysis, where it is more conventional i.e scanline mapping and kinematic analysis by using modern technology i.e drone for photogrammetry mapping. The software used in this project is AgiSoft PhotoScan, Cloud Compare, Discontinuities Set Extractor program in MathLab software, and Dips 7.0 in Rocscience software. As result from empirical analysis, the rock at window A is classified as “poor rock”. Meanwhile kinematic analysis result shows the probability of the rock slope to be a failure is high for wedge and toppling failure but does not occur for planar failure. The major plane of discontinuities is Discontinuity Sets 1 (DS1). Rosette plot of both methods shows the same direction but different in quantity of the discontinuities set. The most dominant direction is N330˚ - N340˚ which trends on NNW-SSE where it describes the major direction of discontinuities while the least dominant discontinuities orientation happens to occur at E-W with the direction of N080˚-N090˚.